Hidradenitis suppurativa/acne inversa: a practical framework for treatment optimization – systematic review and recommendations from the HS ALLIANCE working group. (23rd October 2018) - Zouboulis, C.C.; Bechara, F.G.; Dickinson‐Blok, J.L.; Gulliver, W.; Horváth, B.; Hughes, R.; Kimball, A.B.; Kirby, B.; Martorell, A.; Podda, M.; Prens, E.P.; Ring, H.C.; et al.
Abstract: Hidradenitis suppurativa (HS)/acne inversa is a debilitating chronic disease that remains poorly understood and difficult to manage. Clinical practice is variable, and there is a need for international, evidence‐based and easily applicable consensus on HS management. We report here the findings of a systematic literature review, which were subsequently used as a basis for the development of international consensus recommendations for the management of patients with HS. A systematic literature review was performed for each of nine clinical questions in HS (defined by an expert steering committee), covering comorbidity assessment, therapy (medical, surgical and combinations) and response to treatment. Included articles underwent data extraction and were graded according to the Oxford Centre for Evidence‐based Medicine criteria. Evidence‐based recommendations were then drafted, refined and voted upon, using a modified Delphi process. Overall, 5310 articles were screened, 171 articles were analysed, and 65 were used to derive recommendations. These articles included six randomized controlled trials plus cohort studies and case series. The highest level of evidence concerned dosing recommendations for topical clindamycin in mild disease (with systemic tetracyclines for more frequent/widespread lesions) and biologic therapy (especially adalimumab) as second‐line agents (following conventional therapy failure). Good‐quality evidence was available for the hidradenitis suppurativa clinical response (HiSCR) as a dichotomous outcome measure in inflammatory areas under treatment. Lower‐level evidence supported recommendations for topical triclosan and oral zinc in mild‐to‐moderate HS, systemic clindamycin and rifampicin in moderate HS and intravenous ertapenem in selected patients with more severe disease. Intralesional or systemic steroids may also be considered. Local surgical excision is suggested for mild‐to‐moderate HS, with wide excision for more extensive disease. Despite a paucity of good‐quality data on management decisions in HS, this systematic review has enabled the development of robust and easily applicable clinical recommendations for international physicians based on graded evidence.